Proteomic insights into the biology of dopaminergic neurons - Claudia Cavarischia-Rega; Karan Sharma; Julia C. Fitzgerald; Boris Macek (Frontiers in Molecular Neuroscience)
Dopaminergic neurons, primarily located in the substantia nigra, hypothalamus, and ventral tegmental area of the brain, play crucial roles in motor control, reward, motivation, and cognition. Alterations in their function are associated with numerous neurological and psychiatric disorders, such as Parkinson’s disease, but also Schizophrenia, substance use disorders, and bipolar disorder. Recent advances in mass spectrometry-based proteomics have enabled the comprehensive profiling of protein expression, turnover, subcellular localization, and post-translational modifications at an unprecedented depth of analysis. This review summarizes the developments in proteomic approaches taken to study dopaminergic neurons. We cover findings from global and spatial proteomics studies that revealed brain region-specific protein signatures, as well as dynamic turnover of proteins and the importance of mitochondrial and synaptic proteins for the health and vulnerability of dopaminergic neurons. Combined with advanced molecular cell biology tools, such as growth in microfluidic devices, fluorescent-activated synaptosome sorting, and enzymatic proximity labeling, modern proteomics allows for investigation of synaptic and subcellular proteomes. Despite these advancements, the complexity of the human brain and its cell-specific characteristics remain a challenge. The continuing integration of advanced proteomic techniques with other -omics will eventually yield improved and mechanistic understanding of dopaminergic neurons in health and disease.